The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.cgd.9b00164
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Interactions in Crystals of Soybean Trypsin Inhibitor (Kunitz) Produced by Inclusion of 1,5-Disulfonylnaphthalene

Abstract: In the course of an earlier investigation into the crystallization of proteins based on the addition of intermolecular ligands, the Kunitz type trypsin inhibitor from soybean (SBTI) was crystallized as a complex with 1,5-disulfonylnaphthalene (ligand library 21D). The two molecules within the asymmetric unit of the monoclinic crystals are related by a near-exact NCS 2-fold axis and have essentially the same conformation as was found for them in previous analyses. The protein dimer is maintained through electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The noncompetitive mechanism found for the inhibition of ApTI on the trypsin‐like enzymes of A. gemmatalis agrees with other in silico studies carried out with trypsins from other species of the order Lepidoptera (Migliolo et al, 2010; Ramalho et al, 2018), and the reactive (inhibitory) peptide bond was identified in the alpha chain with the participation of the Arg64 residue and amino acid residues around Pro63, Ile65, and Arg66. This bond is at an exactly homologous position to the reactive sites identified in the soybean inhibitor at Arg‐63‐Ile‐64 (McPherson, Daym, & Larson, 2019) in Albizia at Arg‐66‐I1e‐67 (Sharma, Nath, Kumari, & Bhardwaj, 2012) and in Psophocarpus at Arg‐64‐Ser‐65 (Yamamoto, Hara, & Ikenaka, 1983).…”
Section: Discussionmentioning
confidence: 82%
“…The noncompetitive mechanism found for the inhibition of ApTI on the trypsin‐like enzymes of A. gemmatalis agrees with other in silico studies carried out with trypsins from other species of the order Lepidoptera (Migliolo et al, 2010; Ramalho et al, 2018), and the reactive (inhibitory) peptide bond was identified in the alpha chain with the participation of the Arg64 residue and amino acid residues around Pro63, Ile65, and Arg66. This bond is at an exactly homologous position to the reactive sites identified in the soybean inhibitor at Arg‐63‐Ile‐64 (McPherson, Daym, & Larson, 2019) in Albizia at Arg‐66‐I1e‐67 (Sharma, Nath, Kumari, & Bhardwaj, 2012) and in Psophocarpus at Arg‐64‐Ser‐65 (Yamamoto, Hara, & Ikenaka, 1983).…”
Section: Discussionmentioning
confidence: 82%
“…In legumes, the trypsin inhibitor content ranges from 3 to 84 U/mg, while the chymotrypsin inhibitor content varies from 0 to 17 U/mg [53,54]. The prominent trypsin inhibitors in legumes are the Bowman-Birk inhibitor and Kunitz-type inhibitor (Figure 7) [55][56][57]. Kunitz-type inhibitor (molecular weight 18-24 kDa) and Bowman-Birk inhibitors (molecular weight 7-9 kDa) are both capable of inhibiting trypsin and chymotrypsin enzymes.…”
Section: Protease Inhibitors (Trypsin Inhibitors)mentioning
confidence: 99%